Multidentate Lewis acids: synthesis, structure and mode of action of a redox-based fluoride ion sensor. - Aldridge, S; Bresner, C; Fallis, I; Coles, S; Hursthouse, M (2002)
The mode of action of the bidentate bis(boronate) Lewis acid 2 as a fluoride ion sensor is shown to involve selective anion binding together with an electrochemical response.